Xenotransplantation of neonatal porcine bone marrow–derived mesenchymal stem cells improves diabetic wound healing by promoting angiogenesis and lymphangiogenesis. (12th March 2022) - Yamada, Hideaki; Naito, Reiko; Nishimura, Masuhiro; Kawakami, Ryo; Morinaga, Eri; Morita, Yuichi; Shimizu, Masayuki; Yoshimatsu, Gumpei; Sawamoto, Osamu; Matsumoto, Shinichi; Imafuku, Shinichi; Sakata, Naoaki; et al.
Abstract: Background: Some clinical trials have shown the usefulness of stem cell therapy for diabetic foot ulcers. However, the donor supply is limited, and the process is time consuming and expensive. This study assessed the therapeutic effects of neonatal porcine bone marrow–derived mesenchymal stem cell (npBM‐MSC) xenotransplantation using diabetic wound model mice. Methods: All layers of back skin were removed from streptozotocin‐induced diabetic mice. In the npBM‐MSCs group, npBM‐MSCs were transplanted to the wound, and syngeneic mouse bone marrow–derived mesenchymal stem cells (mBM‐MSCs) were transplanted to the wound in the mBM‐MSCs group. The control group comprised diabetic mice that did not receive cellular therapy. The therapeutic effects of the transplantation were evaluated according to the rate of wound closure and the promotion of neovascularization in the wound. Results: The wound closure rate was significantly improved in the npBM‐MSCs group compared with the control group ( p  < .001 at postoperative day [POD] 4 and p  < .01 at POD 7) and mBM‐MSCs groups ( p  < .05 at POD 4). Prominent promotion of both angiogenesis and lymphangiogenesis was observed in the npBM‐MSCs group. Furthermore, the expression of murine Prox1 and both porcine and murine Vegf s and Tgfb1 in the wounds was enhanced until POD 4 by npBM‐MSCs transplantation. The amounts of vascular endothelial growth factor (VEGF) A, VEGFC, and transforming growth factor β1 secreted from npBM‐MSCs were higher than those from mBM‐MSCs ( p  < .05). Conclusion: Xenotransplantation of npBM‐MSCs improved diabetic wound healing by promoting both angiogenesis and lymphangiogenesis.